The production of sugarcane fiberboard - David, Wilma A. (Animo Repository, 1991)
The study on the viability of using waste bagasse into particleboard has been reviewed, and the apparent effects of the processing parameters on the resultant properties of pagasse and rind board, as generally reported in this study, have been determined.The physical properties such as density, formaldehyde release, springback and surface characteristics are given primary considerations. Also the processing parameters which includes the resin efficiency, adhesive type, pressing conditions are given enough emphasis. More important the strength properties like modulus of rupture, internal bond, face and edge screw holding are the most important factors that were considered in this study if the results is economically feasible or not. Added to this are the moisture and dimensional properties such as water absorption and thickness swelling were given major considerations.The cost of producing the board was also properly evaluated in this study.